1993
DOI: 10.1002/jmv.1890400202
|View full text |Cite
|
Sign up to set email alerts
|

Is the course of perinatal hepatitis B virus infection influenced by genetic heterogeneity of the virus?

Abstract: We studied the relations between genetic heterogeneity of pre-C region of hepatitis B virus (HBV) DNA and outcome of HBV infection in 5 infants with perinatal infection, 3 born to anti-hepatitis B e antigen (HBeAg), and 2 to HBeAg positive mothers. HBV infection developed in the babies at 3-4 months of age, but it resolved with seroconversion to anti-HBs in infants born to anti-HBe positive mothers, while the infection became chronic in the 2 babies born to HBeAg positive mothers. HBV-DNA extracted from the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…However, we reason that the major impediment to monoinfection by genotype G may be its inability to express HBeAg, a molecule believed to play an immunomodulatory function critical for the establishment of persistent infection (10,30). It has been reported that children with maternal transmission of pure wild-type virus became chronically infected, while those infected with a mixture of wild-type virus and an HBeAg-negative mutant resolved the acute infection (35). Similarly, the precore-defective mutant of woodchuck hepatitis virus induced only transient infection in the animals (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, we reason that the major impediment to monoinfection by genotype G may be its inability to express HBeAg, a molecule believed to play an immunomodulatory function critical for the establishment of persistent infection (10,30). It has been reported that children with maternal transmission of pure wild-type virus became chronically infected, while those infected with a mixture of wild-type virus and an HBeAg-negative mutant resolved the acute infection (35). Similarly, the precore-defective mutant of woodchuck hepatitis virus induced only transient infection in the animals (9).…”
Section: Discussionmentioning
confidence: 99%
“…The biological role of HBeAg in the life cycle of the virus remains to be elucidated. It has been suggested that HBeAg secretion may play a pivotal role in the persistence of HBV by inducing immunologic tolerance (20,30,31,42). Certain precore mutants may have an inherent replicative advantage (5,26), although this issue is controversial (12).…”
mentioning
confidence: 99%
“…In these carriers, HBV genome usually harbors mutations that prevent the production of HBeAg (4 -6). These HBeAg-negative variants are often found in acute fulminant rather than chronic HBV infection in neonatal infection and in fulminant hepatitis than in self-limited hepatitis in adult acute infection (7)(8)(9)(10)(11). During chronic infection in some patients, the emergence of HBeAg-negative variants correlates with an exacerbation of liver injury and sometimes even with viral clearance (12)(13)(14)(15).…”
mentioning
confidence: 99%